Pete the cat : crayons rock! - Dean, Kim, 1969-; Dean, James, 1957- (Pete the cat., 2020)
When his friends are less than impressed by the crayon portraits he draws of them, Pete the cat begins doubting his artistic abilities before reconnecting with his unfailingly creative, groovy spirit and the realization that there are no mistakes in art.